Terapia fotodinâmica antimicrobiana aplicada em espécimes de resina acrílica confeccionados em diferentes laboratórios de prótese dentária - Frota, Bruna Marjorie Dias (2012)
This study evaluated the effect of photodynamic therapy on acrylic resin specimens made in different dental prosthetic laboratories. Six laboratories (L), registered in the Regional Council of Dentistry of Ceará, were randomly selected and were not identified to the operator of the experiments. The therapy used erythrosine 22 µM as photosensitizer (P) associated with irradiation with LED of 520 nm, at 38 J/cm2 (L). Fifty specimens of each laboratory were divided into 5 groups (n: 10): sterile positive control in Ethylene Oxide (EO); negative control (P-L-), untreated; control (P+L-) only stained with erythrosine; control (P-L+) only irradiated with 520 nm LED; experimental (P+L+). The specimens were placed in individual tubes containing saline solution and the obtained suspension was diluted and plated on Blood Agar, Sabouraud Dextrose and CHROMagar Orientation®, for incubation within 48 hours at 37°C. The number of colony- forming-units of viable bacteria and yeasts was obtained. The statistical tests of Kruskal-Wallis and Dunn were carried out, which showed a significant difference between the groups (P-L-) and (P+L+) (p <0.0001), identifying contamination with different microorganisms in the six laboratories, such as Enterococcus spp, Pseudomonas spp, Staphylococcus aureus, Klebsiella, Escherichia coli and Staphylococcus saprophyticus. Viable bacteria were eliminated by 100% in laboratories L1, L2, L4 and L5. In laboratories L3 and L6 elimination of viable bacteria was 99%. The viable yeasts were completely eliminated after PDT for laboratories L1, L2, L4 and L5. In the laboratory L3, viable yeast count was reduced by 97% after PDT, whereas in the L6, the reduction was 94%. It was concluded that PDT was effective in microbial removal from the surfaces of the acrylic resin specimens.